Global, regional, and national burdens of lower extremity peripheral arterial disease from 1990 to 2021 and projections to 2050: global burden of disease study 2021 - Zhang, Gaojing; Liu, Xincan; Li, Jianchao; Zhao, Yu; Yuan, Zhiyu; Chen, Yun; Zhang, Shunkai; Chang, Mengxin; Jin, Lili; Tao, Chunjing; Tang, Rongxin; Lan, Zhenzhen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe global and regional burden of lower extremity peripheral artery disease (LEPAD) and its trends have not been systematically studied. Utilizing data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, this study analyses the global burden and associated risk factors for LEPAD from 1990 to 2021 and predicts its incidence trends to 2050.MethodsLEPAD-related data including the number of morbidity, mortality, disability-adjusted life years (DALYs), age-standardized rate (ASR), were extracted from the GBD 2021 database. The analysis assesses the burden stratified by social demographic index (SDI), age, and sex. Bayesian age-period-cohort (BAPC) models were used to predict the future age-standardized incidence.FindingsThe global incidence, death, and DALY of LEPAD increased significantly between 1990 and 2021; however, age-standardized incidence rate (ASIR), age-standardized rates of death (ASMR), and age-standardized disability-adjusted life years (ASDR) have shown an overall decline. In addition, ASIR and SDI were positively correlated. Age-specific analyses revealed that ASMR increased with age. The predictions from the BAPC model indicate a slight increase in ASIR over the next 29 years. While high fasting glucose dominated LEPAD DALYs, summary exposure value (SEV) metrics exposed high Low-Density Lipoprotein Cholesterol (LDL-C) as the primary metabolic exposure burden, highlighting a critical prevention gap.InterpretationThe burden of LEPAD increases progressively with age, and its prevalence is influenced mainly by the SDI. Despite the increased incidence of LEPAD in women, mortality and DALYs were substantially higher in men. The global burden of LEPAD is projected to increase progressively by 2050, representing a major health concern.